Penetapan Tuor Adat di Mandailing Natal dalam Perspektif Hukum Islam - Erma Erma; Muhammad Alwi; Nur Alfiyah; Rahmi Wahyuni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The wedding feast or yuamul farah in each tradition certainly has its distensing or uniqueness that gives birth to the characteristics of each region. The traditions carried out by each tribe of the community are certainly different from one another, one of which is the phenomenon practiced in the traditional events of the Mandailing tribe of North Sumatra which is still attached to this day is the tuor tradition in the Mandailing traditional marriage. Tuor is the name of the marriage dowry in the Mandailing customary agreement. The general description of tuor is: a man is obliged to give tuor to the woman he is going to marry. Tuor is a custom that has existed for a long time. For the people of Mandailing, the practice is as a form of preserving estavet tradition, although some of them do not know the origin of this tradition before. The author's observation on the area can be said that some people agree with the existence of this tuor tradition, but it is undeniable that there are other parts of the community who contradict the practice of the tuor because it can burden the party who will carry out the marriage. The party who feels burdened is the young man who is about to get married. Because sometimes the nominal size of the tuor results in delays in the marriage procession due to economic problems. The result of this study is that the Islamic perspective related to the tour inherited by the Mandailing community is not contradictory, because it is carried out on the basis that it both have aspects of willingness between one party and another. In addition, there is also a sense of family, agreement and also a sense of sincerity between the two sides of the family. The amount of the tuor is no longer a benchmark in Islamic considerations Because the form of the agreement between the two sides became the main foundation in establishing the tour.